Análisis del impacto de la serie de televisión "Isabel" en el turismo cultural de Castilla y León - López Ronco, M. Ángeles; del Caz Martín, Jorge (Geographicalia, 2019)
Queen Isabel of Castile, known as the Catholic, has always been admired and rejected in equal measure. However, in recent years there has been growing interest in knowing about his life and about the places that were part of its story. The birth of this phenomenon is to be found in the success of the television series “Isabel”, broadcast in Spain between 2012 and 2014, which focused on the biography of this queen and showed the different places where she lived. In addition, this had an impact on tourism, adding this fiction to the tendency to use the appearance of a tourist destination in television series as a promotional tool, as it has been demonstrated with the good impact that the series caused in the cultural tourism of Castile and Leon, favouring the growth of the tourist offer of the community and the improvement of the statistics of arrival of visitors.
Keywords: Cultural tourism, route, itinerary, movie tourism, tourist destination, TV series, promotion, visitor.